The Patriotism Values in Main Characters in The Red Cliff Film By John Woo: Sociology of Literature Review 吴宇森对 《赤壁》电影中主角爱国主义价值观：文学社会分析 - Sania Widyastira JP; Intan Erwani (Sinolingua: Journal of Chinese Studies, 2023)
This research discussed the values of the main character in the Chinese movie "The Red Cliff" by John Woo. The goal of this research is to describe the main character's patriotism values as well as the impact that character's patriotism values have on the film. This research is based on Budiyono's patriotism theory. The theoretical basis used is the sociology of literary theory. This research used a descriptive qualitative method and also used listening and note-taking techniques for the data collection. This research also used Miles and Huberman's data analysis method. Based on the analysis of the Red Cliff film, it was found that some data was depicted through the two main characters. Zhūgé Liàng (诸葛亮), the main character, was awarded five data points: self-sacrifice value, courage value, unyielding value, united value, and loyalty value. Zhōu Yú (周瑜), the other main character, received four data points, which were divided into courage value, loyalty value, unyielding value, and unifying value. Thus, John Woo's Red Cliff film proved that the values of patriotism were illustrated by the two main characters.